(untitled) (Bangladesh Journal of Medical Science, 2017)
Visual impairment is one of the most severe sensory restriction of human being. Over the time the situation of visually impaired people changed as well as opportunities in education and tools to live a «normal» independent life. Blindman`s stick, guide dog as well as modern tools as monitors and mobile apps help visually impaired people to become as much as possible integrated in our society. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.10-12